Using a combination of biomarkers to monitor allograft dysfunction in lung transplant recipients - Kattih, Zein; Aryal, Shambhu (Frontiers in Transplantation, 2025)
Allograft dysfunction is a major limitation of survival in organ transplant recipients including those who have received lung transplantation. Early detection of allograft dysfunction is thus crucial to improve outcomes in these patients. However, there are several causes of allograft dysfunction with allograft infection and rejection being the two important causes. It is often difficult to distinguish between those causes as the presentation can be similar. Allograft rejection, especially antibody-mediated rejection (AMR) and chronic lung allograft dysfunction (CLAD) are often identified too late where progression has already occurred. Biomarkers like anti-HLA antibodies including donor-specific antibodies (DSA), donor-derived cell-free DNA (dd-cfDNA), immune cell function (ICF) assays and next-generation sequencing for microorganisms allow for early identification of allograft dysfunction as well as differentiate rejection from other processes such as infection. This in turn allows for early intervention and, ideally, improved long-term allograft outcomes. Greater evidence exists for these biomarkers in other solid organ transplantations including kidney and heart transplantation, but application to lung transplant recipients is increasing and seems equally promising. In this review, we evaluate existing evidence for using these biomarkers and share our center practice in utilizing a combination of these biomarkers post-transplantation to assess for allograft dysfunction.